The Limits of the Civil Judge's Intervention to Restore the Financial Balance of the Contract - Messedek, Fatima-zohra; Bekka, Abdelhafid (Journal of Legal Studies and Researches, 2021)
The authority of the judge to intervene to restore the financial balance of the contract is a power bound by limits, some of which are related to the terms of its implementation, and some are related to the means of restoring the financial balance of the contract, In this study, we will try to clarify the limits of the judge’s intervention in the contract between the necessity to restore the financial balance of the contract and the binding force of the contract represented by the rule “agreements are to be kept”